Residents Perceptions of Tourism Development and Activities: The Case of Mongolia as a Developing Country with a Small Market - Munkhuu, Bilegsaikhan; Sukhragchaa, Amarjargal; Badarch, Lkhamtseden (Jurnal Ilmiah Peuradeun, 2023)
The status of Mongolia’s tourism industry is related to the level of participation of residents and, first of all, their positive and negative perceptions of the impact of tourism. As they are an irreplaceable stakeholder in tourism, they are generally moving towards an approach that involves them in participatory tourism activities. The basic understanding of local people in Mongolia about the impact of tourism, their distinguishing features, and the interrelationship between the effects aims to explain that local people are essential participants in tourism. The survey was conducted in 2021 using a random sampling method with four groups of 10 each and a total of 40 closed-ended questionnaires related to the TDA. A total of 4415 residents participated. As a result of the research, local people perceived the impact of economic, social, cultural, environmental, state, and administrative activities caused by the TDA differently as positive and negative, and these effects were found to be positively and strongly correlated. The current average level of knowledge of residents about the impact of tourism proves that “residents” have become one of the leading players in tourism, and in the future, the concept of “participatory” tourism should be reflected in development plans.